Land Deed Correspondence, Wayne County, 1899 - State of Georgia, Wayne County (Valdosta, GA: Valdosta State University Archives and Special Collections, 2020, 1899)
Land Deed Correspondence, Wayne County, 1899. Typewritten carbon copy record on "W.E. Kay Attorney at Law" stationery. Brunswick, Georgia. To Joseph Hilton on Downing Company Tract of 5000 acres, sold by John A. Foster. Wayne County, Georgia. October 2, 1899. 2 pages.
1 electronic document [PDF/A]. Includes TIFF and JP2 images. Digitized by the Digital Library of Georgia, September 2019.
Keywords: Records and correspondence; Court records; Deeds; Wayne County (Ga.)